What drives social networking users to use mobile commerce? - Barry, Moussa; Jan, Muhammad Tahir (American Scholarly Research Association (ASRA), 2016)
The primary objective of this paper is to develop a conceptual framework that highlights those factors that drive Malaysian social networking users to use mobile commerce. This paper embarked on a qualitative approach to extract those factors from the literature that are considered inevitable for the use of mobile commerce. Previous studies have demonstrated that five main factors, namely: perceived usefulness, perceived ease of use, privacy and security, perceived enjoyment, and behavioural intention have positive effect on mobile commerce use. The proposed model of this study is inspired from Technology Acceptance Model, where some new variables have been added after in-depth review of the extant literature. This paper suggest that in order to enhance the use of mobile commerce among consumers, the mobile commerce providers have to make sure the personal privacy and financial security of consumers are protected. This paper primarily conceptualises a model that would assist in determining the use of mobile commerce. It also provides to the mobile commerce providers recent studies that have been conducted on mobile commerce use. Given that this paper is conceptual paper, there is a need to undertake empirical investigation in order to validate the proposed model of this study, hence further study is recommended.